Anmeldelse af How Dictatorships Work: Power, Personalization, and Collapse - Grundholm, Alexander Taaning (Politica, 2019)
Barbara Geddes, Joseph Wright og Erica Frantz, How Dictatorships Work: Power, Personalization, and Collapse, Cambridge University Press, 2018 (anmeldt af Alexander Taaning Grundholm)